Menelisik Peran IQ, EQ, Dan SQ dalam Kesuksesan Bisnis Generasi Z - Arista Fauzi Kartika Sari; Lilik Purwanti (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
This study aims to examine in more depth how IQ, EQ, and SQ intelligence are practiced by Generation Z in supporting the success of their businesses. As is known, Gen Z is close to technology, and has a high entrepreneurial spirit and creativity. This study is expected to provide a holistic understanding and practical recommendations for the development of sustainable young entrepreneurship. This study uses an interpretive paradigm of the ethnomethodology method by examining three informants with different businesses, but focused on Gen Z who started their own business. The results show that the three informants have integrated IQ, EQ, and SQ to develop their businesses through the indexicality of utilizing technology for marketing, one informant did trial and error. In terms of emotional intelligence (EQ), there is an indexicality of support for other Gen Z, maintaining the mental health of the team, and paying attention to concern for their environment. In terms of spiritual intelligence (SQ), there is an indexicality of belief in the provision of sustenance from God, ensuring the halalness of the products sold, charging prices that are not too high for charity to customers.